THE ONTOLOGY OF LETTERS IN THE SUFISM TRADITION: A STUDY OF RŪZBIHĀN BAQLĪ’S INTERPRETATION OF FAWĀTIḤ AL-SUWAR - Mujahiddin, Anas; Asror, Muhammad (Tanzil: Jurnal Studi Al-Quran, 2026)
This research is motivated because the meaning of the Qur’an is divided into two, namely textual meaning and contextual meaning; The meaning of ẓāhir and the meaning of bāṭin or commonly referred to as explicit meaning and implicit meaning. Therefore, the Qur’an, which contains many diamonds, gems hidden in the ocean of letters, words, and sentences in each of its verses, is open and provides opportunities for new interpretations. This study examines the interpretation of Rūzbihān Baqlī in the style of ishāri’s in Tafsīr ‘Arā’is al-Bayān fī Ḥaqā’iq al-Qur’ān. In addition, this study seeks to answer whether, in its interpretation of the letter al-muqaṭṭa‘ah, there is a dimension of Sufism. In its interpretation, there are variants of interpretation of an object or verse. This research focuses more on the interpretation of the repeated letters al-muqaṭṭa‘ah in the opening of the surahs in the Qur’an. This study is a descriptive-analytical literature study by comparing the interpretation of a series of letters al-muqaṭṭa‘ah that are repeated in one surah with another. As a Sufi, Rūzbihān Baqlī could not avoid his Sufi traits when interpreting the Qur’an, including in interpreting the letters al-muqaṭṭa‘ah. The dimensions of Sufism are found in its interpretation; among these dimensions are ma‘rifah, sitr, tajallī, fanā’, baqā’, shawq, ‘ishq, mushāhadah, ittiḥād, sirr, maḥabbah, and ḥaqīqah.